Instant Personal Branding Calon Legislatif Melalui Instagram - Nurhalimah Nurhalimah; Ade Tuti Turistiati (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2019)
This research aims to analyze the personal branding of M. Yoridho Sinuraya, the legislative candidate for DPRD DKI Jakarta through Instagram. The theory of dramaturgy by Erving Goffman was used to find out personal branding strategy through the employment of the front and backstages of M. Yoridho Sinuraya as a legislative candidate for the Jakarta council (DPRP DKI Jakarta). Based on interviews and observation of Instagram account @sahabatyoridho, it showed that the front stage of M. Yoridho A. Sinuraya had the characteristics of being a friendly, young, pious, and populist man. Meanwhile, the back stage of M. Yoridho A. Sinuraya had characteristics as a young entrepreneur who was lack of interaction with other people and had a semi-formal appearance. The difference between the front and back stages of M. Yoridho A. Sinuraya made him take extra efforts to develop his personal branding, classified as an instant one.